DIGITAL SOLUTIONS OF NEW SPACES FOR CULTURE IN TOURISM OF THE CITY OF VARNA - Popova, Daniela (E-Journal VFU, 2024)
Digitalization presents new ways of responding in the modern world, where green solutions are increasingly important. Digital marketing creates opportunities to carve out a new spatial approach to culture and link it to the tourism of a specific tourist destination. The aim of the paper is to study the investments in the cultural infrastructure of the city of Varna and to adapt new spaces for culture and tourism using the tools of digital marketing.